Joining of Macroscopic 3D Steel Transition Wire Structures to Steel Sheets: Study on the Mechanical, Microstructural, and Phase Characteristics of Brazed and Glued Joints - Saravanan Palaniyappan; Andreas Todt; Maik Trautmann; Felix Röder; Carolin Binotsch; Birgit Awiszus; Guntram Wagner (Metals, 2022)
With an increased demand for the combination of different material classes in lightweight applications like automobiles, aircraft construction, etc., the need for simple and energy-efficient joining technologies to join these different material classes has been extensively researched over the last decades. One such hybrid material combination is the metal–plastic hybrid structure, which offers the combinational characteristics of high strength and stiffness of the metal part along with characteristic elasticity and low density of the plastic part. In this research work, the focus is laid on generating a graded property transition at the interface of metal–plastic joints by brazing a three-dimensional (3D) macroscopic transition wire structure (TWS) strucwire®, over the metal part before being molded with plastic at a later stage using an injection over-molding process. This helps in providing a mechanical interlocking facility and thereby achieving a higher load transfer at the interface of metal–plastic hybrid joints. The graded steel wire structures with different carbon content were brazed onto the galvanized steel sheets using the hotplate brazing technique. In addition to the Zinc layer on the galvanized steel sheets, electroplated Zinc coatings were fabricated on the wire structures to provide better brazing quality. The microstructural, mechanical, and intermetallic phase characteristics of the resulting brazed joints were evaluated using light microscopy, adhesion tests, and scanning electron microscopy, respectively.